Henri Michaux's program for the psychedelic humanities - Davis, Oliver (Frontiers in Psychology, 2023)
This article presents an analytical reading of the extraordinarily rich cultural production around drugs by the 20th-century French poet, writer, critic, and visual artist Michaux (1899–1984). Over about a decade, from the mid-1950's, the otherwise habitually sober Michaux wrote five books, included within which were dozens of drawings, and made one half-hour film, charting his adventures as an initially reluctant yet persistent psychonaut, principally with mescaline, but also with psilocybin, LSD, and cannabis. This has rightly been described as one of the most creative cultural explorations of mescaline. It is more extensive, texturally complex, and esthetically demanding than Aldous Huxley's far better known near-contemporaneous published work on psychedelics in English, which is well-known within and arguably foundational for psychedelic studies. Yet, this very complexity, as well as the national-linguistic context of its articulation—there was no mass psychedelic counterculture in France—have limited wider engagement with it. I argue that Michaux's esthetic reconstruction of psychedelics' effects on his creative brain can be read as a “program” for the emerging field of the psychedelic humanities and that it makes a substantial contribution, which I sketch in outline here, to the following of core concerns: (1) the role of psychedelics in enhancing “creativity”; (2) conceptualization of the politics of psychedelics; and (3) the meaning and value of psychedelic mysticism. I aim to show that Michaux's work on drugs has much to contribute to the cultural understanding of psychedelics today and accordingly that this unjustly neglected classic of French—and global—drug culture deserves to be far better known.